Ocean iron fertilization in the context of the Kyoto Protocol and the post-Kyoto process - Christine Bertram (Kiel Institute for the World Economy (IfW), 2009)
Ocean iron fertilization is currently discussed as a potential measure to mitigate climate change by enhancing oceanic CO2 uptake. Its mitigation potential is not yet well explored, and carbon offsets generated through iron fertilization activities could currently not be traded on regulated carbon markets. Still, commercial interests in ocean iron fertilization already exist, which underlines the need to investigate a possible regulatory framework for it. To this end, I first discuss important basic aspects of ocean iron fertilization, namely its scientific background, quantitative potential, side effects, and costs. In a second step, I review regulatory aspects connected to ocean iron fertilization, like its legal status and open access issues. Moreover, I analyze how the regulations for afforestation and reforestation activities within the framework of the Kyoto Clean Development Mechanism (CDM) could be applied to ocean iron fertilization. Main findings are that the quantitative potential of ocean iron fertilization is limited, that costs are higher than initially hoped, and that potential adverse side effects are severe. Moreover, the legal status of ocean iron fertilization is currently not well defined, open access might cause inefficiencies, and the CDM regulations could not be easily applied to ocean iron fertilization.
Keywords: D62; K33; Q54; Q58; 330; Ocean Iron Fertilization; Kyoto Protocol; CDM; Klimaschutz; Meer; Düngemittel; Stahl; Clean Development Mechanism; Welt